Antecedents of Sustainable Development for Students Pursuing Career in STEM: The Mediating Role of STEM Education - Jindal, Priya; Gupta, Piyush; Shamkuwar, Madhavi; Gupta, Monica (Journal of Engineering Education Transformations, 2025)
Science, technology, engineering and mathematics (STEM) education possesses the capacity to shape the future by developing requisite knowledge and skills needed to find employment and effectively contribute to address the issues of the twenty-first century. It acts as the foundation of individual liberation and collective advancement in a dynamically changing society. This study attempts to delve into the association among skills and re-skills development (SRD), affinity to technology (AFT), outcomes-based education (OBE), and sustainable development (SD). The study also analyzes the mediating role of STEM education in this relationship. Cross-sectional data has been collected from 314 engineering graduates studying in universities in India. Hypotheses testing were done through the covariance-based structural equation modeling (CB-SEM) and mediation analysis was carried out using bootstrap estimation in SPSS AMOS software. The results suggest that SRD and AFT have a significant effect on STEM education and SD. Also, STEM education has a direct impact on SD. Mediation analysis suggests that STEM education has full mediation between the relationship of OBE and SD while partial mediation between AFT and SD. In light of the imminent fourth industrial revolution, it is imperative for sustainable global development that we fully grasp how STEM education can contribute to narrowing the performance gap at the university level and provide great potential for fostering sustainable living.